Some Aspects of the Game Method in Beginner Basketballers Training - Vasile TĂBÎRȚĂ; Serghei SÎRGHI (ACROSS)
Some aspects of the game method approach in the training of beginner basketballers are presented in this article. The game method is one of the most popular and attractive methods, which over the years has proven to be quite effective in training athletes in various sport tests, including sport games. All these aspects make the research topic actual, and the technical training based on the game method, used at the initial stage, should be known by any specialist in the field in order to achieve visible progress in the technical training department and beyond.